Medicinal Plants and Fungi Traditionally Used by Dulong People in Northwest Yunnan, China - Cheng, Zhuo; Hu, Xian; Lu, Xiaoping; Fang, Qiong; Meng, Yuan; Long, Chunlin (Frontiers in Pharmacology, 2022)
The Dulong, an ethnic group living in the isolated Northwest Yunnan of Southwest China, have directly used a wide of plants to serve their needs and have accumulated rich traditional knowledge about medicinal plants over years. Unfortunately, little has been reported about the medicinal plants used by the Dulong people. Ethnobotanical data were collected through semi-structured interviews, guided field trips, and quantitative analysis. Prior informed consent was obtained before each interview. The surveys allowed for the collection of sociodemographic data and traditional knowledge about medicinal plants and their uses. This study used relative frequency of citation (RFC) to identify the most culturally significant medicinal plants and used informant consensus factor (FIC) to evaluate agreement among informants. A total of 105 medicinal plant species belonging to 69 families were recorded. Amongst these 69 families, Asteraceae (8 species), Polygonaceae, Ranunculaceae, and Rosaceae (4 species each) were the dominant families. The whole plants were the most frequently used part (26.6%) in the preparation of medicines. The most common preparation method was decoction (32.8%). The most frequent application route was oral administration (68.6%). Coptis teeta (0.15), Acorus calamus (0.12), Ophiocordyceps sinensis (0.11), Tanacetum tatsienense var. tanacetopsis (0.11), and Paris polyphylla var. yunnanensis (0.08) were shown to be the most useful plants as indicated by their relatively high RFC values. Among the usage types of medicinal plants, the highest FIC values were recorded for the circulatory system (FIC = 0.91), the immune system (FIC = 0.89), and the nervous system (FIC = 0.85). Furthermore, sixty-two medicinal plants utilized by the Dulong for medicinal purposes also have dietary use. Traditional knowledge associated with medicinal plants has been seriously threatened in recent decades. In the future, modern approaches should be used to demystify traditional medicine. However, significant measures need to be taken to protect from loss the important traditional knowledge gained by the Dulong through their experience and inheritance. A collective effort should be made to promote and conserve the important traditional medicinal knowledge and outline a plan for sustainable use of medicinal plants and improve local economic development under the premise of protection.